Gênero, raça/etnia e sexualidade na formação inicial de docentes de Geografia. - Silva, Ritieli Pires da (2023)
The present research seeks to answer the problematic if there is a theoretical, methodological and pedagogical proposal committed to the discussion of gender, race/ethnicity and sexuality in the basic training of Geography teachers. Therefore, it has as main objective to understand how the gender, race/ethnicity and sexuality themes appear in the normative documents of the degree courses in Geography offered by the State System of Higher Education of Paraná, currently composed of seven universities: State University of Londrina (UEL), State University of Ponta Grossa (UEPG), State University of West Paraná (UNIOESTE), State University of Midwest Paraná (UNICENTRO), State University of North Paraná (UENP), State University of Paraná (UNESPAR) and State University of Maringá (UEM). The Hypothesis we have developed was that gender, race/ethnicity and sexuality themes appear in a peripheral way in the basic training of Geography teachers at state universities in Paraná. To get the research objective, we have analyzed the basic training of Geography teachers reality, trying to comprehend how the gender, race/ethnicity and sexuality themes appear in the normative documents of the degree courses in Geography of the universities studies. Through analysis of the Political and Pedagogical Plans of the courses and the subject teaching plans that mention the gender, race/ethnicity and sexuality themes we have built an overview of how these themes appear in the Geography documents courses. Through this analysis, it was possible to observe that UEPG stands out in approaching these themes. However, even with greater emphasis for such themes in Paraná, the compulsory subjects workload intended for the gender, race/ethnicity and sexuality themes comes down to 06 (six) hours. This shows how gender and sexuality themes appear in a shallow way in these professionals' training.